DETERMINATION OF WORK CULTURE AND PERFORMANCE: MOTIVATION ANALYSIS AND INFORMATION TECHNOLOGY (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Renaldi, Alfan (Dinasti International Journal of Digital Business Management, 2022)
Along with the development of technology and high human mobility, the need for fast and easy data and information is standard in today's digital era. Utilization of information technology, both the needs of individuals, groups, and organizations, until almost all sectors of work cannot be separated from the role and function of information technology in terms of helping the work to get better results. This article reviews the Determination of Information Technology and Work Culture: Motivation and Performance Analysis, A Study of Human Resource Management Literature. The results of this research library are that: 1) Motivation affects Work Culture; 2) Motivation affects Work Culture; 3) Motivation affects performance; 4) Information Technology affects performance, and 5) Work Culture has an effect on performance.